Perceived self-efficacy as a mechanism for post-traumatic recovery in Gurnah’s afterlives: the case of Hamza - Salama, Salman Mohamed (Penerbit Universiti Kebangsaan Malaysia, 2024)
This essay aims at reading Abdulrazak Gurnah's Afterlives (2020) as a part of the larger theoretical project of posttraumatic fiction. Within the framework of social cognitive theory, this essay contends that perceived self-efficacy, with its protective function and demonstrable contribution to post-traumatic recovery, enables Hamza, Gurnah's protagonist and a survivor of several traumatic experiences, to exercise some measure of control over his life adversities. Hamza's experiences highlight the substantial relationship between trauma, perceived self-efficacy, and post-traumatic recovery. The analysis leads to the conclusion that Afterlives can productively be considered a work of post-traumatic fiction, both involving and exposing its protagonist's perceived capability to manage his personal functioning in the aftermath of his traumatic experiences. This study not only contributes to literary scholarship by offering a new perspective on Gurnah's work but also provides valuable insights for psychological research on trauma recovery. The paper is divided into several sections: an introduction to Gurnah's work, a literature review of relevant studies, a detailed discussion of the concept of self-efficacy, an analysis of the novel, and a conclusion that ties the findings to contemporary psychological theories. Additionally, this study provides recommendations for future research, suggesting the exploration of self-efficacy in other literary works and examining its application in real-life trauma recovery contexts.